Special Issue “Anaerobes in Biogeochemical Cycles” - Caroline M. Plugge; Diana Z. Sousa (Microorganisms, 2020)
Anaerobic microorganisms, Bacteria and Archaea, have an essential role in global biogeochemical cycles [...]